Spatial aspects as seen from a density analysis of lithics at Middle Pleistocene Qesem Cave: Preliminary results and observations. (4th April 2016) - Gopher, Avi; Parush, Yoni; Assaf, Ella; Barkai, Ran
Abstract: This paper focuses on the results of a preliminary study of flint items densities in different areas and different parts of the stratigrapahic column of Qesem Cave. Qesem Cave is a karst chamber cave with a ∼10 m stratigraphic sequence assigned to the Acheulo-Yabrudian Cultural Complex (AYCC) of the late Lower Paleolithic in the Levant dated to 420–200 ka. We first show the range of lithic densities in studied assemblages in the cave emphasizing significant differences in both the total number of lithic items per volume unit and/or for selected artifact categories within these assemblages. The results are used to suggest differential intensity of lithic-related activities in the cave and variability in synchronic (different areas of the cave within a similar stratigraphic level) distribution aspects of lithic categories of selected assemblages. We briefly note on the diachronic (assemblages belonging to different parts of the stratigraphic sequence) aspect of lithic densities in the discussion, yet this aspect is not is not central in this paper. A comparison of densities to frequency compositions of selected techno-typological categories in the same assemblages/areas further emphasizes the importance of using more than one quantitative measure as a descriptor of lithic assemblages and the interpretative potential of the interplay between the two measures. In some analyzed aspects the differences between the two measures in the same assemblage are quite significant, enabling interpretation of activity areas and specific human behaviors. Eventually, further research testing lithic densities against and/or incorporating them with other sets of density (and frequency) data from the same areas (e.g., faunal remains), or relating these densities to natural (such as a rock shelf) or human made features (such as a fireplace), may offer an elaborate and valuable landscape for reconstructing human behavior at the cave. Furthermore, the spatial distribution of specific techno-typological lithic categories within the assemblages studied as seen in densities augmented by available functional data (derived from use-wear analysis) enable another perspective on the subdivision of activity areas in some parts of the sequence. One synchronic example of our preliminary results which we present relates to generally contemporaneous assemblages adjacent to a constructed fireplace in the center of the cave in the upper part of the lower stratigraphic sequence dated to ca. 300 ka. Both blade-dominated Amudian and Quina (and demi Quina) scrapers dominated Yabrudian assemblages are involved, indicating spatially differentiated, functionally related differences around the fireplace.